Six-minute rowing test: a valid and reliable method for assessing power output in amateur male rowers - Ojeda, Á. H.; Guerra, M. R.; Román, W. C.; Yeomans-Cabrera, M.-M.; Fuentes-Kloss, R. (PeerJ, 2022)
Background: Standardized tests are currently available to assess power output in elite rowers. However, there are no valid and reliable tests to assess power output in amateur rowers. Objective: This study aimed to determine the validity and reliability of a 6-min rowing ergometer test (6-minRT) as a predictor of power output (PO) in amateur male rowers. Methods: Twelve male amateur rowers were part of the study. All participants were instructed to perform an incremental test (IT), a 6-minRT test, and a retest. The validity of the 6-minRT was determined by comparing maximum oxygen uptake (VO2max) and power output (PO) between the IT and 6-minRT. Reliability included the coefficient of variation (CV), intra-class correlation coefficient (ICC), and mean standard error between the 6-minRT test and retest. The significance level was p < 0.05. Results: There was no significant difference in VO2max in both IT and 6-minRT (p = 0.18), while the mean power output (Pmean) generated in the 6-minRT equaled 91.96% of the maximal aerobic power (MAP) generated in the IT (p = 0.004). Reliability analysis for the 6-minRT showed a CV = 0.50% and ICC = 0.97 for distance, a CV = 1.85% and ICC = 0.96 for Pmean. Conclusion: From a ventilatory and mechanical point of view, the 6-minRT is a maximally valid test for establishing MAP in amateur rowers. Also, the 6-minRT evidences a high degree of agreement between days. Therefore, the 6-minRT is a valid and reliable test for assessing PO in amateur male rowers.